Self Regulated Learning dan Konsep Diri sebagai Prediktor Aspirasi Karier pada Remaja - Pratiwi, Rezky Graha; Yuliansyah, Yuliansyah (Jurnal Ilmiah Psyche, 2020)
This study aims to examine the effect of self-regulated learning and self-concept on career aspirations in adolescents. This research uses a quantitative approach with ex-post facto design. This research was conducted in Yogyakarta City which consisted of 223 women and 152 men. Data was collected through CAS-R adaptation for career aspiration scale with 33 items from Obrien (1996), MSLQ for self-regulated learning scale with 44 items from Pintrich and Groot (1990) and TSCS for self-concept scale with 100 items from Fitts (1972) . The category of teenagers who have career aspirations is in the high category. The instrument validation technique uses content validity and Alpha Cronbach coefficient reliability. The results showed that there was an effect of self regulated learning and self-concept on career aspirations in adolescents with a significance value of 0.008 (p <0.05). It can be concluded that Self-regulated learning and self-concept can be strong predictors of career aspirations in adolescent